Bi plasma loaded Bi24O31Br10 nanosheet photocatalyst as well as preparation method and application thereof
By loading BI plasma on the BI24O31 BR10 nanometer, Bi/BI24O31BR10 nanos tablet photocatalyst is prepared, the existing photocatalytic photocatalytic performance is insufficient, and the more efficient photocatalytic degradation effect and anti -light corrosion capacity are achieved.
Patent Information
- Application Number
- CN202411608726.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing photocatalytic degradation of pollutants based on Bi24O31Br10 semiconductor photocatalysts need to be improved, especially in terms of visible light utilization and energy utilization.
By loading Bi plasma on Bi24O31Br10 nanosheets, Bi/Bi24O31Br10 nanosheet photocatalysts were prepared using in-situ reduction methods to improve their photocatalytic performance.
It improves the photocatalytic efficiency of the Bi24O31Br10 nanosheet photocatalyst, enhances the absorption of sunlight, has excellent visible light catalytic degradation of tetracycline in water, and has good resistance to photocorrosion.
Smart Images

Figure CN119346140A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of photocatalytic materials, and in particular relates to a Bi plasma-loaded Bi 24 O 31 Br 10 Nanosheet photocatalyst and its preparation method and application. Background Art
[0002] Antibiotics are widely used to inhibit bacteria and kill bacteria, but they cannot be completely metabolized by humans and animals and are discharged into the environment, causing a lot of pollution. Tetracycline is one of the most widely used antibiotics, and how to degrade it in water environments has become a global problem that urgently needs to be solved.
[0003] Traditional methods for removing tetracycline from water (membrane filtration, flocculation, and biosorption) have disadvantages such as high cost, slow reaction rate, and possible secondary pollution to the environment. Photocatalytic antibiotic oxidation is considered to be a cost-effective and environmentally sustainable method.
[0004] Bismuth oxyhalides (BiOX, X=Cl, Br or I) are widely used in photocatalytic sterilization, degradation of antibiotics, photocatalytic hydrogen production, etc. due to their good visible light photocatalytic performance. 24 O 31 Br 10 Nanosheet photocatalysts. However, single-component photocatalysts have low visible light utilization, and photogenerated electron-hole pairs are prone to recombination, making it difficult to achieve 100% energy utilization. Currently, researchers mainly use methods such as co-catalyst doping, defect regulation, morphology regulation, and heterojunction construction to improve their photocatalytic performance. Bismuth metal (Bi), as a non-precious metal, has a surface plasmon resonance (SPR) effect similar to that of precious metals. It can absorb near-infrared light, and because of its low cost, simple preparation, easy availability, and electron transport, it has great potential to replace precious metals. If the plasma effect of Bi alone can be utilized, Bi 24 O 31 Br 10 The advantages of the nanosheets, such as good visible light catalytic performance, are used to rationally construct Bi-loaded nanosheets containing multiple adsorption sites. 24 O 31 Br 10 Catalysts are expected to achieve the expansion of light response and the enhancement of surface and interface reactions, further improving the efficiency of photocatalytic antibiotic oxidation reactions.
[0005] So far, there is no report on Bi plasma loading. 24 O 31 Br 10 Related research and reports on nanosheet photocatalysts. Summary of the invention
[0006] In view of this, the first object of the present invention is to provide a Bi plasma loaded Bi 24 O 31 Br 10 Nanosheet photocatalysts are used to solve the problems of existing technologies based on Bi 24 O 31 Br 10 There is a technical problem that the photocatalytic degradation performance of pollutants by semiconductor photocatalysts needs to be improved.
[0007] The second object of the present invention is to provide a Bi plasma-loaded Bi 24 O 31 Br 10 Preparation method of nanosheet photocatalyst.
[0008] The third object of the present invention is to provide Bi plasma-loaded Bi 24 O 31 Br 10 Applications of nanosheet photocatalysts.
[0009] To this end, the first technical solution provided by the present invention is as follows:
[0010] A Bi plasma loaded Bi 24 O 31 Br 10 The preparation method of the nanosheet photocatalyst comprises the following steps in sequence:
[0011] At room temperature, the monolithic material Bi 24 O 31 Br 10 Add sodium borohydride solution and stir to carry out reduction reaction for 10 to 60 minutes. The reaction product is post-treated to obtain Bi / Bi 24 O 31 Br 10 Nanosheet photocatalysts;
[0012] The sodium borohydride and Bi 24 O 31 Br 10 The mass ratio is 0.0378~0.00946:0.5.
[0013] The NaBH4 described in this scheme is used to treat the Bi 24 O 31 Br 10 Reduction, part of the Bi in the solution 3+ Converted into metallic Bi loaded on the Bi 24 O 31 Br 10surface, and the oxygen atoms in the lattice escape to form oxygen vacancies.
[0014] Furthermore, the Bi plasma loaded Bi 24 O 31 Br 10 The method for preparing a nanosheet photocatalyst comprises the following steps: the concentration of the sodium borohydride solution is 5 to 20 mmol / L.
[0015] Furthermore, the Bi plasma loaded Bi 24 O 31 Br 10 The method for preparing a nanosheet photocatalyst comprises post-treatment of the reaction product including centrifugal filtration, washing and drying.
[0016] Furthermore, the Bi plasma loaded Bi 24 O 31 Br 10 The method for preparing a nanosheet photocatalyst comprises the following steps: adding sodium borohydride into deionized water at 3°C and stirring the solution uniformly.
[0017] The second technical solution provided by the present invention is a Bi plasma-loaded Bi prepared by the method described in the first technical solution. 24 O 31 Br 10 Nanosheet photocatalysts.
[0018] Furthermore, the above-mentioned Bi plasma-loaded Bi 24 O 31 Br 10 Nanosheet photocatalysts, including Bi 24 O 31 Br 10 Nanosheets and nano-Bi; the Bi 24 O 31 Br 10 The nanosheets carry the nano-Bi.
[0019] The third technical solution provided by the present invention is the above-mentioned Bi / Bi 24 O 31 Br 10 Application of nanosheet photocatalysts in photocatalytic degradation of pollutants in water.
[0020] Furthermore, the above Bi / Bi 24 O 31 Br 10 The invention discloses an application of a nanosheet photocatalyst in photocatalytic degradation of pollutants in water, wherein the organic pollutants are tetracycline, ciprofloxacin, chlortetracycline hydrochloride or methyl orange.
[0021] The last technical solution provided by the present invention is a Bi / Bi 24 O 31 Br 10 The method for photocatalytic degradation of pollutants in water by nanosheet photocatalysts comprises: at a pH value of 3.0 to 9.0, a Bi / Bi solution having a concentration of 15 to 30 mg / L is added to the solution; 24 O 31 Br 10 The nanosheet photocatalyst is added to a system containing organic pollutants and photocatalytically degrades the organic pollutants under the irradiation of a xenon lamp.
[0022] Furthermore, the above-mentioned Bi / Bi 24 O 31 Br 10 The method of photocatalytic degradation of pollutants in water by nanosheet photocatalysts is to convert Bi / Bi with a concentration of 20 mg / L into water at a pH value of 5.4. 24 O 31 Br 10 The nanosheet photocatalyst is added to a system containing organic pollutants and photocatalytically degrades the organic pollutants under the irradiation of a xenon lamp.
[0023] Furthermore, the above-mentioned Bi / Bi 24 O 31 Br 10 A method for photocatalytically degrading pollutants in water using nanosheet photocatalysts, wherein ascorbic acid is also added to the system of organic pollutants.
[0024] Compared with the prior art, the Bi / Bi 24 O 31 Br 10 Nanosheet photocatalysis has the following advantages and beneficial effects:
[0025] (1) The present invention uses an in-situ reduction method to prepare a new Bi / Bi 24 O 31 Br 10 The nanosheet photocatalyst composite photocatalyst has the advantages of simple preparation process, convenient operation, low cost, good repeatability and low energy consumption.
[0026] (2) The Bi plasma in the technical solution provided by the present invention can suppress Bi / Bi 24 O 31 Br 10 The electron-hole pair recombination rate of nanosheet photocatalysts increases Bi 24 O 31 Br 10 The migration and separation efficiency of photogenerated carriers can improve the Bi / Bi 24 O 31Br 10 Photocatalytic efficiency of nanosheet photocatalysts and Bi / Bi 24 O 31 Br 10 Nanosheet photocatalysts have a narrower band gap than monolayer materials, which can enhance the intramolecular charge transfer in the material and further enhance the Bi / Bi 24 O 31 Br 10 Absorption of sunlight by nanosheet photocatalysts.
[0027] (3) The technical solution Bi / Bi provided by the present invention 24 O 31 Br 10 Nanosheet photocatalysts tend to generate holes and superoxide radicals after being irradiated with light, and Bi plasma and oxygen vacancies can synergistically improve Bi / Bi 24 O 31 Br 10 The migration and separation efficiency of photogenerated carriers of the nanosheet composite photocatalyst enable it to have excellent performance in visible light catalytic degradation of tetracycline in water, and has good performance in catalytic degradation of organic pollutants in the full spectrum, and has good application prospects.
[0028] (4) In the technical solution provided by the present invention, Bi / Bi 24 O 31 Br 10 Nanosheet photocatalysts add anions HCO3 to water in the photocatalytic degradation of pollutants in water - Bi that helps increase Bi loading 24 O 31 Br 10 The degradation rate of the nanosheet photocatalyst is not affected by the anion SO4 in the water. 2- 、NO3 - drastically decreased due to the impact.
[0029] (5) In the technical solution provided by the present invention, Bi / Bi 24 O 31 Br 10 Nanosheet photocatalysts have a stable structure and excellent resistance to photocorrosion. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Bi / Bi 24 O 31 Br 10 Transmission electron microscopy (TEM) images of nanosheet photocatalysts: (a) Bi 24 O 31 Br 10 Nanosheet (b)Bi / Bi24 O 31 Br 10 -5(c)Bi / Bi 24 O 31 Br 10 -10(d)Bi / Bi 24 O 31 Br 10 -20;
[0031] Figure 2 Bi / Bi 24 O 31 Br 10 Scanning electron microscope (SEM) images of nanosheet photocatalysts: (a) Bi 24 O 31 Br 10 Nanosheet (b)Bi / Bi 24 O 31 Br 10 -5(c)Bi / Bi 24 O 31 Br 10 -10(d)Bi / Bi 24 O 31 Br 10 -20;
[0032] Figure 3 Bi / Bi 24 O 31 Br 10 XRD pattern of nanosheet photocatalyst;
[0033] Figure 4 It is the photocatalytic degradation efficiency of the samples on tetracycline and the kinetic analysis of the photocatalytic degradation of tetracycline by the samples;
[0034] Figure 5 The experimental results of photocatalytic degradation of tetracycline under different conditions: (a) The effect of free radical scavengers on the photocatalytic degradation effect of catalysts (b) Bi / Bi under different pH conditions 24 O 31 Br 10 -20 photocatalytic degradation efficiency of tetracycline (c) different masses of Bi / Bi 24 O 31 Br 10 The photocatalytic degradation efficiency of tetracycline by -20 (d) is Bi / Bi at different tetracycline concentrations. 24 O 31 Br 10 -20 photocatalytic degradation efficiency;
[0035] Figure 6 Bi / Bi 24 O31 Br 10 -20 Experimental results of exploring other properties and applications of materials: (a) Stability test results of catalyst under continuous light (b) Bi / Bi 24 O 31 Br 10 Photocatalytic degradation rate of tetracycline by -20 material under near infrared spectrum and full spectrum (c)Bi / Bi 24 O 31 Br 10 Photocatalytic degradation effect of Bi / Bi-20 materials on ciprofloxacin, chlortetracycline hydrochloride and methyl orange (d) 24 O 31 Br 10 Photocatalytic degradation efficiency of tetracycline by -20 material in different lake water samples. DETAILED DESCRIPTION
[0036] The technical solution of the present application will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0037] Example 1
[0038] The present application embodiment provides a Bi / Bi 24 O 31 Br 10 The preparation method of the nanosheet photocatalyst comprises the following steps in sequence:
[0039] Add 0.0378 g of sodium borohydride to 50 mL of deionized water at 3 °C and mix well to obtain a NaBH4 solution with a concentration of 5 mmol / L. Then weigh 0.5 g of the monometallic material Bi 24 O 31 Br 10 Place it in NaBH4 solution, stir it at room temperature for ten minutes, wash it with ethanol and deionized water once, and finally dry it in an oven at 70℃ for 12h to obtain Bi / Bi 24 O 31 Br 10 Nanosheet photocatalyst (Bi / Bi 24 O 31 Br 10 -5).
[0040] Example 2
[0041] The present application embodiment provides a Bi / Bi 24 O 31 Br 10The preparation method of the nanosheet photocatalyst comprises the following steps in sequence:
[0042] Add 0.0189 g of sodium borohydride to 50 mL of deionized water at 3 °C and mix well to obtain a NaBH4 solution with a concentration of 10 mmol / L. Then weigh 0.5 g of the monometallic material Bi 24 O 31 Br 10 The prepared NaBH4 solution was placed in the solution and stirred at room temperature for ten minutes, then washed with ethanol and deionized water once, and finally dried in an oven at 70°C for 12 hours to obtain Bi / Bi 24 O 31 Br 10 Nanosheet photocatalyst (Bi / Bi 24 O 31 Br 10 -10).
[0043] Example 3
[0044] The present application embodiment provides a Bi / Bi 24 O 31 Br 10 The preparation method of the nanosheet photocatalyst comprises the following steps in sequence:
[0045] Add 0.00946 g of sodium borohydride to 50 mL of deionized water at 3 °C and mix well to obtain a NaBH4 solution with a concentration of 20 mmol / L. Then weigh 0.5 g of the monometallic material Bi 24 O 31 Br 10 The prepared NaBH4 solution was placed in the solution and stirred at room temperature for ten minutes, then washed with ethanol and deionized water once, and finally dried in an oven at 70°C for 12 hours to obtain Bi / Bi 24 O 31 Br 10 Nanosheet photocatalyst (Bi / Bi 24 O 31 Br 10 -20).
[0046] Bi described in Examples 1-3 24 O 31 Br 10 Prepared by the following method:
[0047] Dissolve 2.14g of bismuth nitrate pentahydrate in 20mL of ethylene glycol and stir vigorously with a magnetic stirrer for 22min to form a uniform solution A. Add 1.958g of ammonium bromide to 50mL of pure water and stir vigorously with a magnetic stirrer for 6min to form a uniform solution B. After mixing solutions A and B, add 2.4mL of ethanolamine and stir for ten minutes. Load the mixed solution into a polytetrafluoroethylene-lined autoclave, transfer it to a muffle furnace, and heat it at 160°C for 12h. After the reaction is completed, wash the precipitate alternately with alcohol and pure water three times, and dry it in an oven at 70°C for 6h to obtain the monomaterial Bi 24 O 31 Br 10 .
[0048] In order to demonstrate the advantages of the technical solution provided by the present application, the experimental detection spectrum and data of the technical solution provided by the present application are given below:
[0049] Compare 24 O 31 Br 10 、Bi / Bi 24 O 31 Br 10 The nanosheet photocatalyst was subjected to X-ray diffraction spectroscopy analysis, and the results are as follows Figure 3 As shown, from Figure 3 It can be seen that the magnetic stirring physically mixes the monolithic material Bi 24 O 31 Br 10 and NaBH4 solution to load Bi onto Bi 24 O 31 Br 10 Nanosheet photocatalyst surface, prepared Bi / Bi 24 O 31 Br 10 Nanosheets, low cost, good reproducibility, low energy consumption
[0050] For the monolithic material Bi in step 1 24 O 31 Br 10 、Bi / Bi 24 O 31 Br 10 The nanosheet photocatalyst was analyzed by electron microscopy, and the results are as follows Figure 1-2 As shown in the figure, it can be seen that Bi / Bi 24 O 31 Br 10 The nanosheet photocatalyst maintains its original ultra-thin sheet structure, the nanosheets overlap and are evenly dispersed, and the nano-Bi is evenly dispersed in the Bi 24 O 31 Br 10The nanosheet substrate shows the Bi / Bi 24 O 31 Br 10 The nanosheets are regular in shape, overlapped and evenly dispersed, and the nano-Bi is evenly distributed, stably attached and not easy to fall off, thus making Bi / Bi 24 O 31 Br 10 Nanosheet photocatalysts have excellent photocatalytic activity.
[0051] Test Example 1
[0052] This test example is to test the Bi / Bi prepared in Examples 1, 2, and 3. 24 O 31 Br 10 The performance of the nanosheet photocatalyst in degrading tetracycline under photocatalytic conditions. The test includes the following steps: preparing tetracycline solution, Bi / Bi 24 O 31 Br 10 Nanosheet photocatalyst dark adsorption experiment and Bi / Bi 24 O 31 Br 10 Test of photocatalytic degradation of tetracycline by nanosheet photocatalyst.
[0053] Step 1, preparing a tetracycline solution comprises the following steps: preparing a 1 g / L tetracycline solution in advance, taking 1 mL of the 1 g / L tetracycline solution and adding it to 49 mL of deionized water, and performing sufficient ultrasonic treatment and oscillation mixing before use, at which time the concentration of the tetracycline solution is 20 mg / L.
[0054] Step 2. Bi / Bi 24 O 31 Br 10 The dark adsorption experiment of nanosheet photocatalysts includes the following steps: first, add 50 mL of 20 mg / L tetracycline solution into a double-layer beaker, and use a water circulation cooler to maintain the system at a constant temperature of 25 °C; after the temperature of the tetracycline solution system stabilizes, add 10 mg of Bi / Bi 24 O 31 Br 10 Catalyst, immediately wrap the beaker with tin foil and conduct a dark adsorption experiment for 30 minutes.
[0055] Step 3. Bi / Bi 24 O 31 Br 10The test of photocatalytic degradation of tetracycline by nanosheet photocatalyst includes the following steps: After dark adsorption is completed, the tin foil is removed and the solution is exposed to a 300W xenon lamp equipped with a 420nm UV cutoff filter as the light source for the photocatalytic reaction. Under illumination conditions, 3mL of the reaction solution sample is taken out at 20, 40, 60, 80, 100, and 120 minutes. After each sampling, the catalyst in the solution is filtered out using a 0.22μm filter membrane. Subsequently, the absorbance of the solution is measured at 357nm using a UV-vis spectrophotometer, and all data are collected and collated to evaluate the degree of degradation of tetracycline.
[0056] The results are as follows Figure 4 As shown, from Figure 4 (a) It can be seen that when the illumination is 120 minutes, the monolithic material Bi 24 O 31 Br 10 It showed good tetracycline degradation efficiency, with a tetracycline degradation rate of about 60%; while Bi / Bi 24 O 31 Br 10 The degradation efficiency of tetracycline by nanosheet photocatalyst is higher than that of single-element material Bi 24 O 31 Br 10 The degradation efficiency has been further improved, and the degradation efficiency has been significantly improved with the increase of Bi loading on the catalyst surface. 24 O 31 Br 10 -20 (i.e., the Bi / Bi prepared by using 20 mmol / L NaBH4 solution in Example 4) 24 O 31 Br 10 Nanosheet photocatalysts) have the best degradation performance. Figure 4 (b) also shows Bi / Bi 24 O 31 Br 10 -20 has an excellent rate constant.
[0057] Test Example 2
[0058] This test example is the Bi / Bi prepared in test example 3. 24 O 31 Br 10 -20 nanosheet photocatalyst was used to perform free radical scavenging experiment on tetracycline degradation under photocatalytic conditions. The test included the following steps: preparing tetracycline solution and three parallel experiments with different free radical quenchers added.
[0059] Step 1, preparing a tetracycline solution comprises the following steps: preparing a 1 g / L tetracycline solution in advance, taking 1 mL of the 1 g / L tetracycline solution and adding it to 49 mL of deionized water, and performing sufficient ultrasonic treatment and oscillation mixing before use, at which time the concentration of the tetracycline solution is 20 mg / L.
[0060] Step 2: Three parallel experiments with different free radical quenchers included:
[0061] Group 1, 10 mg of Bi / Bi 24 O 31 Br 10 -20 catalyst and 6.7 mg sodium oxalate were added into 50 mL 20 mg / L tetracycline solution and mixed well.
[0062] Group 2, 10 mg of Bi / Bi 24 O 31 Br 10 -20 catalyst and 0.5 mL of isopropanol were added to 50 mL of 20 mg / L tetracycline solution and mixed well.
[0063] Group 3, 10 mg of Bi / Bi 24 O 31 Br 10 -20 catalyst and 8.8 mg ascorbic acid were added to 50 mL of 20 mg / L tetracycline solution and mixed well.
[0064] The results are as follows Figure 5 As shown in (a), Figure 5 (a) It can be seen that in the experimental group without the addition of free radical scavengers, the photocatalytic degradation effect of the catalyst on tetracycline was relatively normal; while in the experimental group with the addition of ascorbic acid (Vc), the degradation efficiency of the catalyst on tetracycline was significantly reduced. Ascorbic acid mainly captured the superoxide radicals in the solution, which indirectly indicated that the main ROS generated by the catalyst was superoxide radicals.
[0065] Test Example 3
[0066] This test example is the Bi / Bi prepared in test example 3. 24 O 31 Br 10 A single-factor experiment was conducted to determine the optimal conditions for tetracycline catalysis using a 20-nanosheet photocatalyst. The test included the following steps: experimental groups with different pH values, experimental groups with different catalyst doses, and experimental groups with different tetracycline concentrations.
[0067] Step 1. Set up four experimental groups with different pH values, and adjust the pH values to 3, 5, 7, and 9 respectively. And take samples before and after each adjustment to ensure that the change in pH value does not affect the absorbance of tetracycline. Then add the catalyst to the tetracycline solution with adjusted pH value to conduct degradation experiment. At this time, the concentration of tetracycline solution is 20 mg / L.
[0068] Step 2. Three groups of catalyst single-factor experiments were designed, and each experimental group used 5 mg, 15 mg, and 20 mg of catalyst respectively. Before the experiment, the catalysts of different masses were weighed using a precision balance. Then, under the same experimental conditions as the photocatalytic degradation of tetracycline, the catalysts were evenly dispersed in a 10 mg / L tetracycline solution, and stirred continuously to ensure that the catalyst and tetracycline could fully contact and react, and finally the degradation of tetracycline was collected.
[0069] Step 3: Add 0.75 mL of 1 g / L tetracycline solution to 49.25 mL of pure water to prepare a tetracycline concentration of 15 mg / L. Similarly, to obtain concentrations of 25 mg / L and 30 mg / L, add 1.25 mL and 1.5 mL of 1 g / L tetracycline solution to the corresponding amount of pure water, respectively. During the experiment, the total volume of the reaction system was kept constant at 50 mL. The photocatalytic degradation experiment was carried out using the prepared solution under the same conditions, and the degradation of tetracycline was finally collected.
[0070] The results are as follows Figure 5 As shown, from Figure 5 (b) It can be seen that when the pH value of tetracycline is 5.4, the catalyst has the best degradation effect on tetracycline. Figure 5 (c) It can be seen that 10 mg of the catalyst can produce the best degradation effect on 50 mL, 20 mg / L tetracycline solution; Figure 5 (d) It can be seen that in the lower concentration of tetracycline solution, Bi / Bi 24 O 31 Br 10 -20 showed a higher degradation efficiency. As the concentration of tetracycline increased, Bi / Bi 24 O 31 Br 10 The degradation efficiency of -20 began to decrease. This experimental result is helpful for the subsequent exploration of Bi / Bi 24 O 31 Br 10 Optimal conditions for tetracycline degradation by -20
[0071] Test Example 4
[0072] This test example is the Bi / Bi prepared in test example 3. 24 O 31 Br10 -20 nanosheet photocatalyst stability experiment, the test includes the following steps: using the same material to carry out photocatalytic cycle degradation of tetracycline experiment.
[0073] Step 1. After the first tetracycline degradation experiment is completed, the remaining tetracycline solution is centrifuged to separate the catalyst and tetracycline. After centrifugation, the catalyst material is carefully collected and placed in an oven for drying. Weigh 10 mg of the dried material to perform a photocatalytic degradation experiment on tetracycline again. After the experiment, the remaining catalyst in the tetracycline solution is collected using the same method. Finally, the dried catalyst is used to perform a third photocatalytic degradation experiment. After each round of stability test experiments, the degradation rate of the catalyst to tetracycline is recorded.
[0074] The results are as follows Figure 6 As shown in (a), Figure 6 (a) It can be seen that Bi / Bi 24 O 31 Br 10 -20 had a higher degradation efficiency in the first cycle experiment. However, in the subsequent second and third cycle degradation experiments, the degradation efficiency of tetracycline decreased, but the decrease was not significant, indicating that Bi / Bi 24 O 31 Br 10 -20 can still maintain most of its activity after repeated use.
[0075] Test Example 5
[0076] This test example is the Bi / Bi prepared in test example 3. 24 O 31 Br 10 -20 Full spectrum illumination experiment of nanosheet photocatalyst, the test includes steps: Bi / Bi 24 O 31 Br 10 -20 Full spectrum illumination experiment of nanosheet photocatalyst.
[0077] Step 1. Before the experiment, replace the cold reflector of the xenon lamp with a full reflector. The full reflector has a stronger reflectivity than the cold reflector, which can further expand the spectral range of the xenon lamp and simulate a wider range of solar spectrum illumination. In addition to changing the light source conditions, other experimental conditions are consistent with the previous experimental conditions for photocatalytic degradation of tetracycline, and the amount of catalyst and the concentration of tetracycline remain unchanged at 10 mg and 20 mg / L.
[0078] The results are as follows Figure 6 As shown in (b), Figure 6 (b) It can be seen that Bi / Bi 24 O 31 Br10 The -20 material showed degradation activity throughout the entire spectral range, especially in the ultraviolet light region, but the results of the full-spectrum illumination experiment did not achieve the expected effect. Under full-spectrum illumination, the degradation efficiency of tetracycline was not significantly improved.
[0079] Test Example 6
[0080] This test example is the Bi / Bi prepared in test example 3. 24 O 31 Br 10 -20 nanosheet photocatalyst for the degradation of other pollutants, the test includes the steps: Bi / Bi 24 O 31 Br 10 -20 nanosheet photocatalyst degradation experiment for other pollutants.
[0081] Step 1. The experimental conditions are consistent with those for tetracycline degradation: 50 mL of reaction system, 25°C ambient temperature, and 120 minutes of illumination. In terms of pollutant concentration control, the concentrations of other pollutants such as ciprofloxacin, chlortetracycline hydrochloride, and methyl orange are consistent with those of tetracycline, with an initial concentration of 10 mg / L.
[0082] The results are as follows Figure 6 (c) shows that from Figure 6 (c) It can be seen that Bi / Bi 24 O 31 Br 10 -20 has a very good degradation effect on ciprofloxacin. After 120 minutes of illumination, the degradation rate of ciprofloxacin by the catalyst is as high as 93%. In comparison, the degradation rate of the catalyst for chlortetracycline hydrochloride and methyl orange is lower. The dark adsorption effect of the catalyst on these two is better than that of tetracycline, and the photocatalytic effect is smaller. After 120 minutes of illumination, the degradation rate of the catalyst for chlortetracycline hydrochloride and methyl orange is between 40% and 50%.
[0083] Test Example 7
[0084] This test example is the Bi / Bi prepared in test example 3. 24 O 31 Br 10 -20 nanosheet photocatalyst actual water degradation experiment, the test includes the following steps: collecting and treating lake water samples, dark adsorption experiment, Bi / Bi 24 O 31 Br 10 -20 nanosheet photocatalyst actual water degradation experiment.
[0085] Step 1: The lake water sample was collected by plastic bottles and initially filtered using filter paper to remove suspended particles in the water sample. Subsequently, the filtered lake water sample was used to prepare a solution containing tetracycline, and the initial concentration of tetracycline was set to 20 mg / L.
[0086] Step 2. Bi / Bi 24 O 31 Br 10 The dark adsorption experiment of -20 nanosheet photocatalyst includes the following steps: first, add 50mL of 20mg / L tetracycline solution into a double-layer beaker, and use a water circulation cooler to maintain the system at a constant temperature of 25°C; after the temperature of the tetracycline solution system stabilizes, add 10mg of Bi / Bi 24 O 31 Br 10 -20 catalyst, immediately wrap the beaker with tin foil and conduct a dark adsorption experiment for 30 minutes.
[0087] Step 3. Bi / Bi 24 O 31 Br 10 The test of photocatalytic degradation of tetracycline by -20 nanosheet photocatalyst includes the following steps: After dark adsorption is completed, the tin foil is removed and the solution is exposed to a 300W xenon lamp equipped with a 420nm UV cutoff filter as the light source for the photocatalytic reaction. Under illumination conditions, 3mL of the reaction solution sample is taken out at 20, 40, 60, 80, 100, and 120 minutes. After each sampling, the catalyst in the solution is filtered out using a 0.22μm filter membrane. Subsequently, the absorbance of the solution is measured at 357nm using a UV-vis spectrophotometer, and all data are collected and collated to evaluate the degree of degradation of tetracycline.
[0088] The results are as follows Figure 6 As shown in (d), Figure 6 (d) It can be seen that Bi / Bi 24 O 31 Br 10 -20 catalyst showed good tetracycline degradation performance in the actual lake water environment. After 120 minutes of illumination, the degradation rates of tetracycline in the lake water samples of the Central Lake and the Scenic Lake reached about 60% and 75%, respectively, confirming that Bi / Bi 24 O 31 Br 10 -20 has the potential in practical water treatment applications.
[0089] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A Bi plasma loaded Bi 24 O 31 Br 10 The method for preparing a nanosheet photocatalyst is characterized in that: The steps are as follows: At room temperature, the monolithic material Bi 24 O 31 Br 10 Add sodium borohydride solution and stir to carry out reduction reaction for 10 to 60 minutes. The reaction product is post-treated to obtain Bi / Bi 24 O 31 Br 10 Nanosheet photocatalysts; The sodium borohydride and Bi 24 O 31 Br 10 The mass ratio is 0.0378~0.00946:0.
5.
2. The Bi plasma-loaded Bi according to claim 1 24 O 31 Br 10 The method for preparing a nanosheet photocatalyst is characterized in that: The concentration of the sodium borohydride solution is 5-20 mmol / L; the method for preparing the sodium borohydride solution is to add sodium borohydride into deionized water at 3° C. and stir evenly.
3. The Bi plasma-loaded Bi according to claim 1 24 O 31 Br 10 The method for preparing a nanosheet photocatalyst is characterized in that: The post-treatment of the reaction product includes centrifugal filtration, washing and drying.
4. A Bi plasma loaded Bi 24 O 31 Br 10 Nanosheet photocatalyst, characterized in that The method is prepared by any one of claims 1 to 4.
5. The Bi plasma-loaded Bi according to claim 4 24 O 31 Br 10 Nanosheet photocatalyst, characterized in that Including Bi 24 O 31 Br 10 Nanosheets and nano-Bi; the Bi 24 O 31 Br 10 The nanosheets carry the nano-Bi.
6. The Bi / Bi according to claim 1 24 O 31 Br 10 Application of nanosheet photocatalysts in photocatalytic degradation of pollutants in water.
7. The Bi / Bi according to claim 6 24 O 31 Br 10 The application of nanosheet photocatalyst in photocatalytic degradation of pollutants in water is characterized in that: The organic pollutant is tetracycline or ciprofloxacin or chlortetracycline hydrochloride or methyl orange. 8.A kind of Bi / Bi 24 O 31 Br 10 The method for photocatalytic degradation of pollutants in water by nanosheet photocatalysts is characterized in that: At a pH value of 3.0 to 9.0, add 15 to 30 mg / L Bi / Bi 24 O 31 Br 10 The nanosheet photocatalyst is added to a system containing organic pollutants and photocatalytically degrades the organic pollutants under the irradiation of a xenon lamp.
9. The Bi / Bi according to claim 1 24 O 31 Br 10 The method for photocatalytic degradation of pollutants in water by nanosheet photocatalysts is characterized in that: At pH 5.4, a concentration of 20 mg / L Bi / Bi 24 O 31 Br 10 The nanosheet photocatalyst is added to a system containing organic pollutants and photocatalytically degrades the organic pollutants under the irradiation of a xenon lamp.
10. The Bi / Bi according to claim 1 24 O 31 Br 10 The method for photocatalytic degradation of pollutants in water by nanosheet photocatalysts is characterized in that: The system of organic pollutants is also added with ascorbic acid.
Citation Information
Patent Citations
Bi / BiOCl (bismuth oxychloride) composite photocatalyst as well as in-situ reduction preparation method and application thereof
CN103908973A
Bi / Bi4O5Br2 photocatalyst as well as preparation method and application thereof
CN113976147A
Oxygen-vacancy-enriched Bi / Bi12O17Cl2 nanoflower photocatalyst as well as preparation method and application thereof
CN118059895A
Sunflower-shaped Bi24O31Cl10 photocatalyst as well as preparation method and application thereof
CN118162173A